2013
DOI: 10.1037/a0030947
|View full text |Cite
|
Sign up to set email alerts
|

Rapid forgetting prevented by retrospective attention cues.

Abstract: Recent studies have demonstrated that memory performance can be enhanced by a cue which indicates the item most likely to be subsequently probed, even when that cue is delivered seconds after a stimulus array is extinguished. Although such retro-cuing has attracted considerable interest, the mechanisms underlying it remain unclear. Here, we tested the hypothesis that retro-cues might protect an item from degradation over time. We employed two techniques that previously have not been deployed in retro-cuing tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
309
5
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(351 citation statements)
references
References 41 publications
32
309
5
5
Order By: Relevance
“…In these studies, colored retrocues identified one of several colored objects held in memory and participants reproduced their orientation (Heuer & Schubö, 2016;Li & Saiki, 2015;Pertzov et al, 2013). The observed advantage of valid retro-cues was comparable to that of spatial retro-cues in terms of its time course and the size of the effect (Pertzov et al, 2013), although it had a different spatial profile (Heuer & Schubö, 2016). Nevertheless, observers may have used the feature retro-cue to guide spatial attention to the remembered item's location (cf.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In these studies, colored retrocues identified one of several colored objects held in memory and participants reproduced their orientation (Heuer & Schubö, 2016;Li & Saiki, 2015;Pertzov et al, 2013). The observed advantage of valid retro-cues was comparable to that of spatial retro-cues in terms of its time course and the size of the effect (Pertzov et al, 2013), although it had a different spatial profile (Heuer & Schubö, 2016). Nevertheless, observers may have used the feature retro-cue to guide spatial attention to the remembered item's location (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, observers may have used the feature retro-cue to guide spatial attention to the remembered item's location (cf. Pertzov et al, 2013). We meticulously designed our stimuli to pre-empt any spatial strategy to solve the task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations